A high resolution extreme ultraviolet spectrometer system optimized for harmonic spectroscopy and XUV beam analysis - Wuensche, Martin; Fuchs, Silvio; Weber, Thomas; Nathanael, Jan; Abel, Johann J.; Reinhard, Julius; Wiesner, Felix; Huebner, Uwe; Skruszewicz, Slawomir J.; Paulus, Gerhard G.; Roedel, Christian (Review of Scientific Instruments, 2019)
We present a modular extreme ultraviolet (XUV) spectrometer system optimized for a broad spectral range of 12-41 nm (30-99 eV) with a high spectral resolution of λ/Δλ 784 ± 89. The spectrometer system has several operation modes for (1) XUV beam inspection, (2) angular spectral analysis, and (3) imaging spectroscopy. These options allow for a versatile use in high harmonic spectroscopy and XUV beam analysis. The high performance of the spectrometer is demonstrated using a novel cross-sectional imaging method called XUV coherence tomography.
CRIS-Team Scopus Importer:2023-04-20